The relative importance of tree and stand properties in susceptibility to spruce beetle outbreak in the mid‐20th century - Bakaj, Felicia; Mietkiewicz, Nathan; Veblen, Thomas T.; Kulakowski, Dominik (Ecosphere (Washington, D.C), 2016)
Tree susceptibility to potentially lethal agents is determined not only by attributes of individual trees, but also by neighborhood effects at a range of scales. For example, effects of disturbances on individual trees are often contingent on the size, configuration, and other properties of neighboring trees. Wildfires can modify postfire properties of individual trees as well as of entire forest stands, both of which can affect subsequent ecological processes, including subsequent disturbances. In recent years, much has been learned about how disturbances interact, but numerous questions concerning underlying mechanisms remain unresolved. For example, the relative importance of forest properties at different spatial scales in determining how fires affect forest susceptibility to subsequent disturbances is not well understood. This study explicitly compares the relative importance of tree vs. fine‐scale neighborhood effects (e.g., stand properties at <7 m radii), on susceptibility to a 1940s' spruce beetle outbreak. Attributes of individual trees and of stand structure were spatially reconstructed at five 250‐m2 sites that were partly burned in the late 19th century and then affected by spruce beetle outbreak in the 1940s. Random Forest models and classification trees were used to compare the relative importance of variables for susceptibility to spruce beetle attack. Individual tree properties (diameter at breast height and age) were the most important predictors of susceptibility to the outbreak across all sites combined and at each of the sites individually. In contrast, neighborhood effects were poor predictors of susceptibility. This study suggests wildfires reduce susceptibility to outbreaks primarily by reducing the size of postfire live trees and only secondarily by modifying stand structure. One implication of this is that management strategies that aim to modify stand structure over large areas in order to reduce susceptibility to spruce beetle outbreaks may be unnecessarily intensive.